(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The experiment was conducted to evaluate the effect of Moisture regimes and inoculation on growth and yield of Bambara groundnut in dry season of 2021/2022 at irrigation farm of College of Agriculture and Animal Science, Mando Kaduna and Institute for Agricultural Research IAR, A.B.U., Samaru-Zaria, both located in the Northern Guinea Savannah Ecological Zone of Nigeria respectively. Treatments consisted of four levels of moisture regimes (25%, 50%, 75%, and 100%) and two levels of inoculation; no inoculation and inoculation. Treatment were factorially combined in a randomized complete block design (RCBD) and replicated three times. Data on growth parameter were collected on number of leaves, number of branches, net assimilation rate, days to 50% flowering and kernel yield kg/ha were collected. Results showed that 100% moisture regime significantly resulted in highest growth indices like number of leaves, number of branches, net assimilation rate, days to 50% flowering and kernel yield kg/ha of Bambara groundnut over other regimes evaluated. While inoculation of Bambara groundnut significantly resulted in higher performance in both growth and yield parameters evaluated over non-inoculated Bambara groundnut plants. From the results obtained, the combination of 100% moisture regimes produced better performance on growth and yield of inoculated Bambara groundnut at both locations.